Assessment of Growth Reduction of Five Clinical Pathogens by Injectable S53P4 Bioactive Glass Material Formulations - Thijssen, Eline G. J.; van Gestel, Nicole A. P.; Bevers, Raymond; Hofmann, Sandra; Geurts, Jan; van Loo, Inge H. M.; Arts, J. J. (Frontiers in Bioengineering and Biotechnology, 2020)
The one-stage treatment of chronic osteomyelitis with S53P4 bioactive glass (BAG) granules has shown excellent results. However, these granules possess suboptimal handling properties. Therefore, new injectable S53P4 putty materials have been developed by the incorporation of a synthetic binder to contain glass granules. The goal of the current study was to assess their potential to eradicate five clinically relevant pathogens: methicillin sensitive Staphylococcus aureus (MSSA), methicillin resistant Staphylococcus aureus (MRSA), Enterococcus coli (E. coli), Enterococcus faecalis (E. faecalis), and Pseudomonas aeruginosa (P. aeruginosa). As a control, S53P4 granules (500-800 µm) and S66 glass (< 45 µm) were used. To evaluate the antimicrobial properties, the materials were cultured with the pathogens in a Müller-Hinton II broth for a week with daily colony forming unit (CFU) counting. One of the tested putty formulations was observed to reduce the number of CFU/mL compared to a negative control (no material, only pathogen in broth) for E. coli, E. faecalis and P. aeruginosa. However, none of the tested putty formulations was able to completely eradicate the pathogens in the broths, which would be needed for safe infection treatment. The results obtained for the control materials were unexpected. S66 glass showed full eradication of P. aeruginosa and reduced the number of CFUs of other pathogens, while the S53P4 granules did not show eradication. The observations on the loose S53P4 granules in this study contradict available literature, which needs further investigation. The results obtained in this study also stretch the importance for a better understanding of the underlying antimicrobial mechanism of S53P4 BAG and how this is related to the dosage. In addition, it should be elucidated how these antimicrobial properties are affected by changes in the material formulation, for example by addition of binders to improve the handling properties or by changing the surface area.